BASIC AREAS OF THE POLYGRAPH USE IN THE MINISTRY OF DEFENSE AND THE ARMED FORCES OF UKRAINE - Малюга, В.; Гришин, С.; Малюга, В. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article highlights the features of the polygraph use in the Ministry of Defense and the Armed Forces of Ukraine. The most effective areas of application of personnel survey using the polygraph in the Ministry of Defense and the Armed Forces of Ukraine in modern conditions have been justified and analyzed. Key words: Polygraph, survey with the use of polygraph, personnel, personnel security, Ministry of Defense of Ukraine, the Armed Forces of Ukraine, polygraph testing, screening, official investigations.